Influence of light filters in intraocular lenses on color perception and contrast acuity. Issue 6 (June 2015) - Wissiak, Elfriede; Ardjomand, Navid; Steinwender, Gernot; Prskavec, Martin; Baradaran‐Dilmaghani, Ramin; Kohl, Maria; Wirtitsch, Matthias G.
Abstract : Purpose : To compare contrast acuity at different illumination levels, color vision, and the subjective visual impression in patients after bilateral cataract surgery with mixed implantation of a yellow‐tinted intraocular lens (IOL) and an orange‐tinted IOL. Setting : Department of Ophthalmology, Hietzing Hospital, Vienna, Austria. Design : Prospective case series. Methods : Consecutive patients with age‐related cataract had standardized small‐incision cataract surgery with IOL implantation in the capsular bag. Patients were randomly assigned to receive a yellow Polylens Y30 in 1 eye and an Orange Series model PC 440Y in the contralateral eye. The main outcome measures were contrast acuity, color vision, and subjective visual impression. Contrast acuity was measured at illumination levels of 5.0 lux and 0.5 lux and contrast levels of 50.0%, 25.0%, and 12.5%. Color vision was assessed using the Heidelberg‐multicolor anomaloscope, and the subjective visual impression was evaluated using a questionnaire. Results : This study included 64 eyes of 32 patients. The intraindividual comparison showed no significant difference in contrast sensitivity at different contrast and illumination levels or in color vision. On questioning, 3 patients reported a difference in subjective color perception between the 2 IOL types. Conclusion : There were no differences in contrast sensitivity or color vision between yellow‐tinted IOLs and orange‐tinted IOLs. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.